Popularity Ranking of Undergraduate Thesis Manuscripts in the E-Read System Based on Number of User Accesses (Future Science, 2021)
The undergraduate thesis is a scientific work produced by a final year student who collaborates with his supervisor as a condition to be able to complete his studies at a university. The increase in the number of thesis works has caused the library at the Faculty of Computer Science, UPN